Cultural Sensitivity in Family Research: Bridging Gaps - Rostami, Mehdi; Navabinejad, Shokouh (Journal of Psychosociological Research in Family and Culture, 2023)
We are writing to address the crucial issue of cultural sensitivity in family research and the necessity to bridge gaps and expand horizons in this area. The significance of cultural sensitivity in family research cannot be overstated, as it plays a pivotal role in ensuring the provision of effective and inclusive family-centered care. This letter aims to synthesize and integrate relevant literature to underscore the importance of cultural sensitivity in family research and to advocate for the adoption of culturally sensitive approaches in this domain. The existing literature underscores the critical importance of cultural sensitivity in family research and the provision of family-centered care. The integration of culturally sensitive approaches in family research and healthcare practices is essential to bridge gaps and expand horizons, ensuring the inclusivity and effectiveness of services provided to diverse families. It is imperative for researchers, practitioners, and policymakers to prioritize cultural sensitivity in family research and healthcare to foster an environment of inclusivity and equity.